Un, deux, ou quatre… : Les écoles de relations internationales - Korany, Bahgat (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
The thesis of this paper is that despite the so-called breakthrough in the study of International Relations following the behavioral revolution of the 1960s, this field is still Anglo-saxon, particularly American-centered. The paper's emphasis then is on the widening of International Relations as a field of analysis and the bringing in of differing approaches so that this field becomes truly universal as its name indicates. To review the evolution of this field, the paper is divided into two main parts of unequal length. The short part one review s Kuhn's scheme concerning the different stages in the evolution of science. The long part two applies this scheme to the study of International Relations and characterizes it as in a state of crisis, because of its lack of a consensual paradigm to guide analysis and research. It emphasises that the division between schools is not only methodological, but especially epistemological and ideological. Consequently, the paper analyses in detail the different arguments of four schools : Realism, Behavioralism, Marxism, and Neo-Marxism and Dependencia.